American Cleft-Palate Craniofacial Association Annual Meeting: International Medical Graduate's Perspective as a First-Time Attendee. (October 2019) - Abu-Ghname, Amjed; Maricevich, Renata S.
In the United States, plastic surgery continues to be one of the most competitive fields to match into for medical graduates. However, the process is even more difficult for international medical graduates (IMGs) mostly due to their unknown academic backgrounds and unfamiliarity with US health-care system. While many IMGs pursue of research to publish articles in peer-reviewed journals and obtain letters of recommendations as a means to prove one's potential, networking with well-known plastic surgeons in US plastic surgery programs via national meetings is of utmost importance. These conferences provide the perfect opportunity to learn about the multidisciplinary US health-care system, expand one's network of mentors and colleagues, and demonstrate one's research experience. This article describes my experience as a first-time attendee in the American Cleft-Palate Craniofacial Association 76th Annual Meeting, with the aim to encourage other IMGs interested in applying to plastic surgery residency programs to actively pursue and attend national plastic surgery society meetings.